A Case Study on Bulking Problems in Paper Recycling Effluent Treatment Plant in Malaysia - Redzwan, G.; Ying, L.L.S.; Ibrahim, S.; Annuar, M.S.M. (IOS Press, 2008)
This study was conducted to investigate the cause of bulking problem at the effluent treatment plant (ETP) of a paper recycling plant in Malaysia. Hypothetically, the effluent is lacking nutrients and could induce the overpopulation of filamentous bacteria, and further cause the bulking problem during the effluent treatment using activated sludge process. Experiment to simulate treatment operations had been set up at laboratory. The simulation showed that the bulking started to occur after the first cycle of the fed-batch operation with the typical effluent. To make up the lacking of nutrients in the effluent, urea (N) and phosphate (P) were added as supplements with the ratio of BOD:N:P equal to 100:1.0:0.7. The supplemented effluent was again tested by a simulation study and showed that the bulking problem started to take place after the third cycle of feeding regime. Bulking problem also periodically took place in the actual operation when the same supplemented formula was applied; however the frequency of occurrence was lesser. Therefore, this study has shown that other than the lack of nutrients, there are other factors that could cause bulking problem.